On psychoanalysis during the COVID-19 pandemic - Rakić Glišić, Vida (Engrami, 2021)
The COVID-19 pandemic is becoming unfortunately traumatic for many, which is especially what authors from the USA and Israel are writing about, and which often manifests itself in our country, faced us on a personal and collective level with the crisis as a chance and a challenge for the emergence and deepening of awareness of basic values ​​in life, for the emergence and deepening of a sense of gratitude for the basic things we have in life, but also for the analytical processing of earlier and the earliest personal and collective traumas that the actual trauma brought to the surface and allowed us to approach them.Commitment to working with patients means keeping our mental world and the mental world of our patients working together all the time, even before, after and during turbulences. That work involves discovering the patient's life force because, especially in a critical, crisis, stressful age, the role of creativity is essential. The psychotherapist's creativity also changes under the influence of the pandemic, as does his / her ability to trigger his / her own anxieties and fear of death.Therefore now, during this crisis, we are giving to the unconscious its place more than ever. It is important that we all the time maintain and nurture listening to the unconscious with our patients. This is a basic principle in the face of trauma, and the current pandemic provides a chance to relive all the trauma.
Keywords: Psychoanalysis; COVID-19; pandemic